A new species of Lissodendoryx (Anomodoryx) Burton, 1934 (Porifera: Demospongiae: Poecilosclerida) from deeper waters off the Atlantic coast of Brazil - Cavalcanti, Thaynã; Santos, George Garcia; Pinheiro, Ulisses (Zootaxa, 2014)
The members of Lissodendoryx Topsent, 1892a are recognized by a spicule combination of ectosomal tylotes or strongyles, isodictyal reticulate architecture, arcuate isochelae and sigmas (Hofman & Van Soest 1995; Van Soest 2002). Five subgenera of Lissodendoryx, are recognized (Van Soest 2002): Lissodendoryx (Acanthodoryx) Lévi, 1961, L. (Anomodoryx) Burton, 1934, L. (Ectyodoryx) Lundbeck, 1909, L. (Lissodendoryx) Topsent, 1892a, and L. (Waldoschmittia) de Laubenfels, 1936. Lissodendoryx (Anomodoryx) is defined by the presence of a single megasclere type (Van Soest 2002). Currently has six recognized species (Van Soest et al. 2014) including two from Brazil (Muricy et al. 2011): L. (A.) recife (Boury-Esnault, 1973) and L. (A.) tylota (Boury-Esnault, 1973). In this paper, a new species of L. (Anomodoryx) is described from the mesophotic zone off Bacia Potiguar (Rio Grande do Norte State, Northeastern Brazil). The specimen was preserved in ethanol 80% and deposited in the Porifera Collection of the Universidade Federal de Pernambuco (UFPEPOR).